71 Outcome in patients undergoing high-risk pci using impella circulatory support - 10 year experience. (May 2019) - Vetrugno, Vincenzo; Waqas, Muhammad; Sandhu, Kulwinder; Mechery, Anthony; Nadir, M. Adnan; George, Sudhakar; Zaphiriou, Alexander; Lim, Sern; Ludman, Peter; Doshi, Sagar; Townend, Jonathan; khan, sohail
Abstract : Introduction: The use of Impella in the setting of high-risk percutaneous coronary intervention (PCI) has been introduced in clinical practice in the last few years in selected hospitals, giving a chance for revascularization to a sensible number of patients who are usually unsuitable for cardiac surgery due to high risks. In addition, some of these patients present pre-procedural cardiogenic shock, further increasing the rate of morbidity and mortality. Our purpose was to assess outcome of patients undergoing Impella-assisted high-risk PCI in our 10 year experience and to assess possible predictors of adverse events. Methods: From May 2008 to September 2018 patients undergoing Impella-assisted high-risk PCI were enrolled. Clinical, laboratory, echocardiographic, angiographic and procedural data were collected. Coronary artery disease burden was graded using the British Cardiovascular Intervention Society Jeopardy Score (BCIS-JS). In-hospital MACCE were recorded. During routine follow-up visits data including MACCE, hospital admissions for heart failure, Canadian Cardiovascular Society (CCS) angina grade and New York Heart Association (NYHA) functional class were recorded. Long-term survival Kaplan Meier analysis was performed according to national registry death data. Results: A total of 80 consecutive patients were enrolled (71.2±13.7 years, male gender 73.8%), 21 (26.3%) presenting with stable angina, 53 (66.3%) with NSTE-ACS and 6 (7.5%) with STEMI. 67 (83.8%) of them showed multivessel disease, 42 (52.5%) unprotected left main disease, 47 (58.8%) severe left ventricle systolic dysfunction (LVEF<30%), 10 (12.5%) pre-procedural cardiogenic shock. Median BCIS-JS was 10 [8, 00; 12, 00]. In-hospital MACCE occurred in 16 (20%) patients with death in 15 (18.8%). Median time to first follow-up visit for survivors was 105 (64.5; 282.0) days: at this time 11 (13.8%) patients had MACCE, 3 (3.8%) had hospital admissions for heart failure, median CCS was 0.00 (0.00; 0.00) and median NYHA was 1.00 (1.00; 2.00). Mean survival time (procedure to death, months) was 21 months (C.I. 14.4 - 29.0). Multivariate logistic regression analysis for possible predictors of in-hospital MACCE was performed including the variables showing a p value <0.100 at univariate analysis, i.e. pre-procedural cardiogenic shock [OR 9.00, C.I. (2.1–37.6), p=0.003] and CK peak [OR 1.00, C.I. (1.0–1.0), p=0.051]. Pre-procedural cardiogenic shock was the only predictor [OR 7.058, C.I. (1.2–40.6), p=0.029] of in-hospital MACCE. No significant predictors of MACCE at follow-up were found at logistic regression analysis. Conclusion: In our 10 year experience of Impella-assisted high-risk PCI, 20% patients had in-hospital MACCE and mean survival was 21 months. At follow up, MACCE rate was less than 4% and both angina and heart failure symptoms were well controlled. Pre-procedural cardiogenic shock was the only predictor of in-hospital MACCE. Conflict of Interest: No conflict of interest